1999
DOI: 10.1021/jf9806309
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Acetaldehyde-Induced Condensation of (−)-Epicatechin and Malvidin 3-O-Glucoside in a Model Solution System

Abstract: The reaction between (-)-epicatechin, malvidin 3-O-glucoside, and acetaldehyde was studied in a model solution system. Ethyl-linked flavanol oligomers and anthocyanin-flavanol derivatives were observed, showing that the two polyphenols competed in the condensation process. Among the anthocyanin-ethyl-flavanol adducts, dimeric compounds in which the flavanol was linked to the anthocyanin with CH(3)-CH bridges were observed. In addition, trimeric and tetrameric products containing one anthocyanin and one, two, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
184
2
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 219 publications
(199 citation statements)
references
References 22 publications
11
184
2
2
Order By: Relevance
“…Trimeric and tetrameric pigments have been identified, but only position C8 of the anthocyanin molecule can be involved in this reaction, with the polymerisation ceasing when the anthocyanin forms the two terminal products of the chain. However, recent evidence suggests that the C6 position of the anthocyanin can also be reactive, as anthocyanins in the absence of flavanols formed dimers, trimers and tetramers via ethyl bonds with each other when acetaldehyde was added (Es-Safi et al, 1999a;Atanosova et al, 2002b). This reaction, which is faster than the previous two, takes place during barrel ageing when controlled oxygenation takes place.…”
Section: Effect Of Oxygen On Red Wine Colourmentioning
confidence: 99%
“…Trimeric and tetrameric pigments have been identified, but only position C8 of the anthocyanin molecule can be involved in this reaction, with the polymerisation ceasing when the anthocyanin forms the two terminal products of the chain. However, recent evidence suggests that the C6 position of the anthocyanin can also be reactive, as anthocyanins in the absence of flavanols formed dimers, trimers and tetramers via ethyl bonds with each other when acetaldehyde was added (Es-Safi et al, 1999a;Atanosova et al, 2002b). This reaction, which is faster than the previous two, takes place during barrel ageing when controlled oxygenation takes place.…”
Section: Effect Of Oxygen On Red Wine Colourmentioning
confidence: 99%
“…This initial decrease in h* can be ascribed to the formation of purple acetaldehyde-mediated condensation products (Timberlake & Bridle, 1976;Rivas-Gonzalo et al, 1995). The subsequent increase in h* is attributed to the formation of orange-red pyranoanthocyanins (Fulcrand et al, 1996; or further reaction of ethyl-linked pigments to form larger, brown polymers (Es-Safi et al, 1999a) or yellow xanthylium pigments (Es-Safi et al, 1999b). Alcalde-Eon et al (2006) reported an increase in pyranoanthocyanin content in Tempranillo wine during oak maturation (six months) and the subsequent period of bottle ageing.…”
Section: Figurementioning
confidence: 99%
“…When large amounts of lowermolecular-weight phenolic compounds (eg, anthocyanins and flavanol monomers) are present, random cleavage and subsequent addition reactions result in reduction of the average size of tannins and derived species (46,47). Ethyl-linked flavanols also undergo acid-catalyzed cleavage at wine pH values (48). Reaction of the intermediates thus released with anthocyanins leads either to ethyl-linked flavanol anthocyanin adducts (48) or to flavanyl-pyranoanthocyanins (49) (Figure 4, R ҃ flavanyl).…”
Section: S Cheyniermentioning
confidence: 99%
“…Ethyl-linked flavanols also undergo acid-catalyzed cleavage at wine pH values (48). Reaction of the intermediates thus released with anthocyanins leads either to ethyl-linked flavanol anthocyanin adducts (48) or to flavanyl-pyranoanthocyanins (49) (Figure 4, R ҃ flavanyl). All of these processes take place simultaneously, with their respective kinetics depending on the proportions of phenolic precursors (which are themselves determined by the grape composition and extraction process) and also on several other factors, including the concentrations of some nonphenolic compounds (eg, aldehydes), oxygen exposure and the presence of oxidation catalysts, pH, and temperature.…”
Section: S Cheyniermentioning
confidence: 99%